The Role of Teachers in Increasing Motivation to Learn Arts and Culture Subjects for Class IV SDN 1 Tanantovea - Usnia, Usnia; Lagandesa, Yun Ratna; Lapasere, Sisriawan; Dewi, Andi Imrah; Rahmaeni M, Andi (Journal of Educational Sciences, 2025)
Learning motivation is an important factor that influences student success, especially in the subject of Arts, Culture and Crafts (SBdP) which requires creativity. This study aims to describe the role of teachers in improving the learning motivation of fourth grade students of SDN 1 Tanantovea in the subject of SBdP. The method used is descriptive qualitative with data collection techniques through observation, interviews, documentation, and questionnaires. The results of the study showed that teachers act as facilitators, learning managers, motivators, guides, and demonstrators. Based on the results of the questionnaire, 53.3% of students strongly agreed and 46.7% agreed that teachers make SBdP learning more enjoyable. As many as 60% of students agreed that teachers are always ready to guide when students experience difficulties. teachers use a variety of learning media, provide motivation, individual guidance, and deliver materials in an interesting way. With the active and creative involvement of teachers, the SBdP learning process becomes more meaningful and is able to foster student learning motivation optimally. This study concludes that the role of teachers is very significant in fostering students' interest in learning so that it can improve learning outcomes in fourth grade of SDN 1 Tanantovea.